Principles of Oocyte and Embryo Donation - Sauer, Mark V.; Sauer, Mark V. (Springer London : Imprint: Springer, 2013)
The versatility of oocyte and embryo donation has proven to be extremely valuable to both patients and doctors engaged in reproductive medicine. Originally thought to be applicable only to a rather small subset of infertile women, today busy practices commonly recommend the procedure and it is estimated that nearly all of the 400 or more IVF programs in the United States provide these services. Oocyte and embryo donation has established itself as a mainstay procedure within assisted reproductive care, and the breadth, depth and complexity of practice is deserving of focused attention. Much has changed within the field of oocyte and embryo donation since the publication of the first edition of Principles of Oocyte and Embryo Donation in 1998, thus the need for a completely updated and more expansive text. The second edition of this book provides an overview of the major issues affecting men and women engaged in the practice of oocyte and embryo donation.  A primary emphasis has been placed on defining the standards of practice that have evolved over the past 30 years, clearly stating the outcomes expected from adhering to these established protocols.  Details of both the basic science and the clinical medicine are presented together and attention is also focused on the non-reproductive aspects inherent to this unique method of assisted reproduction that involves opinions from lawyers, ethicists, mental health care professionals and theologians.  Oocyte and embryo donation requires a working knowledge of the medicine, the law and the ethics that underlies its foundation. This book is intended to serve as a complete and comprehensive reference for all health care professionals that provide services related to egg donation, reproductive endocrinologists, obstetrician- gynecologists, and fellows and residents entering the fertility field.